Biological Risk in the Mexican Population at the Turn of the 21(st) Century - Beltrán-Sánchez, Hiram (2013)
Mexico has experienced changes in its demographic and epidemiologic profile accompanied by recent changes in nutrition and income. Thus, the old and the young have experienced very different environments. Using data from the Mexican National Health Nutrition Survey 2006, we examine age and sex differences in physiological status and dysregulation and assess how socioeconomic factors associate with variability in biological indicators of health. Results indicate that young people have experienced better physical development as evidenced by their being taller and having less stunting. There is currently little under-nutrition in Mexico, but there is evidence of over-nutrition as indicated by high prevalence of overweight across the age range. Physiological dysregulation across multiple systems is higher in Mexicans than Americans across all ages. Mexicans have: higher levels of blood pressure, plasma glucose, and especially for women, dysregulated cholesterol and higher body weight. Low education is associated with both being stunted and overweight, and with adverse levels of HDL cholesterol and more physiological risk factors. Rural dwelling males are less likely to be overweight as are females living in poor states. Living in a poor state among females and having rural residence among males is associated with a higher number of high-risk factors. Overweight is a strong predictor of hypertension. Age differences in indicators of physiological development suggest that the epidemiological and demographic transitions in Mexico were accompanied by improved physical development; however, increases in nutrition may have reached a point of diminishing returns as Mexico switched from a state of under-nutrition to over-nutrition.